Crime Prevention in Southern Africa and the Caribbean Regions - Christopher Nuttall (My University, 2016)
Document seeks to meet a distinct development impact by recommending to the read practical action to prevent crime in Southern Africa and Caribbean--two regions that suffer greatly from violent crime.